2016
DOI: 10.1002/qj.2816
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the latent heating contribution to foehn warming: Lagrangian analysis of two foehn events over the Swiss Alps

Abstract: Foehn flows are typically associated with warm air temperatures. Though several theories for the so‐called foehn air warming have been developed over the past century, no conclusion about the most important mechanism has been reached. The development of new methods to calculate accurate air‐mass trajectories over complex topography has opened up a new perspective on this question. Air‐mass‐trajectories derived from wind‐field data from COSMO model simulations with 20 s temporal resolution are used in this stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
58
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(70 citation statements)
references
References 38 publications
10
58
2
Order By: Relevance
“…First, the isentropic drawdown is the dominant factor over both Mountain Ranges X and Y in this study. Several studies demonstrate the importance of this mechanism for mountains ranges in the Alps, Iceland, and Antarctica (Seibert, ; Grosvenor et al, ; Elvidge et al, ; Würsch and Sprenger, ; Miltenberger et al, ). Elvidge and Renfrew () indicated that radiative heating did not contribute as much to warming as other mechanisms.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…First, the isentropic drawdown is the dominant factor over both Mountain Ranges X and Y in this study. Several studies demonstrate the importance of this mechanism for mountains ranges in the Alps, Iceland, and Antarctica (Seibert, ; Grosvenor et al, ; Elvidge et al, ; Würsch and Sprenger, ; Miltenberger et al, ). Elvidge and Renfrew () indicated that radiative heating did not contribute as much to warming as other mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…In the textbook föhn effect case, relatively warm and moist air blows nearly perpendicular to the topographic barrier, and then either flows over the mountain or is blocked, leading to the cold air damming on the upwind side. However, the föhn effect is more complicated in the real world, and there is no general theory that can be applied to each case (Miltenberger et al, ). The strength of the lee‐side warming is significantly related to the dominant mechanisms generating the föhn effect.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An offline analysis would follow the traditional approach of saving all necessary fields on disk (e.g., with a temporal resolution of 1 h) and then running the diagnostic. In contrast, an online analysis would be run as part of the main model forward integration, allowing for an almost arbitrary temporal resolution of input fields-for example, online forward trajectory calculations (Miltenberger et al 2016). In the following, two applications are considered, with differing requirements in terms of the temporal resolution and data volume of the input fields.…”
Section: E579mentioning
confidence: 99%
“…Advection of potentially warmer and drier air from aloft towards the surface generates the föhn conditions (Elvidge & Renfrew, ). Turbulent sensible heating, mechanical mixing of air on the lee slope, and increased incoming solar radiation from cloud‐clearing can also enhance föhn warming (Miltenberger et al ). In this study, two methods of detection have been used to identify föhn conditions from observations and from the Antarctic Mesoscale Prediction System (AMPS).…”
Section: Introductionmentioning
confidence: 99%